Plasma profiling reveals three proteins associated to amyotrophic lateral sclerosis. (14th July 2014) - Häggmark, Anna; Mikus, Maria; Mohsenchian, Atefeh; Hong, Mun‐Gwan; Forsström, Björn; Gajewska, Beata; Barańczyk‐Kuźma, Anna; Uhlén, Mathias; Schwenk, Jochen M.; Kuźma‐Kozakiewicz, Magdalena; Nilsson, Peter
Abstract Objective Amyotrophic lateral sclerosis (ALS) is the most common adult motor neuron disease leading to muscular paralysis and death within 3–5 years from onset. Currently, there are no reliable and sensitive markers able to substantially shorten the diagnosis delay. The objective of the study was to analyze a large number of proteins in plasma from patients with various clinical phenotypes of ALS in search for novel proteins or protein profiles that could serve as potential indicators of disease. Methods Affinity proteomics in the form of antibody suspension bead arrays were applied to profile plasma samples from 367 ALS patients and 101 controls. The plasma protein content was directly labeled and protein profiles obtained using 352 antibodies from the Human Protein Atlas targeting 278 proteins. A focused bead array was then built to further profile eight selected protein targets in all available samples. Results Disease‐associated significant differences were observed and replicated for profiles from antibodies targeting the proteins: neurofilament medium polypeptide (NEFM), solute carrier family 25 (SLC25A20), and regulator of G‐protein signaling 18 (RGS18). Interpretation Upon further validation in several independent cohorts with inclusion of a broad range of other neurological disorders as controls, the alterations of these three protein profiles in plasma could potentially provide new molecular markers of disease that contribute to the quest of understanding ALS pathology.